Significance of the inframammary crease for reconstruction of the breast and methods for its restoration (a review of literature) - I. F. Kamaletdinov; A. Kh. Ismagilov (ABV-press, 2015)
The use of tissue expanders thanks to its simplicity and efficacy is the most common method of breast reconstruction today. However,the common problem during this procedure is lack of the inframammary crease (IMC) that is disrupted during radical treatment for cancer, which prevents the achievement of symmetry with the contralateral breast. IMC is an important component of the attractive aesthetically normal appearance of the breast, since it plays a considerable role in the formation and maintenance of its shape; it is one of the most important elements of the natural manifestation of breast ptosis and ensures the lower support for subpectorally located endoprostheses, which keeps them from malposition. If the IMC is slightly pronounced, asymmetrically located, or displaced in the postoperative period, it virtually negatively affects all other contours, including the shape of the upper and lower poles, the position of the breast on the chest, and the degree of symmetry with the contralateral breast. Thus, the development and mastering of the surgical techniques, which reconstruct properly and hold the position of this structure, is an urgent component of successful reconstructive surgery. This paper analyzes the significance of IMC for reconstruction of the breast and also reviews current methods for its restoration.